Pharmacological Treatment of Sarcopenia Tratamento medicamentoso da sarcopenia - Caio Gonçalves de Souza (Revista Brasileira de Ortopedia, 2020)
Abstract Sarcopenia has been acquiring a growing importance in the scientific literature and in doctors’ offices. As the population ages, it becomes increasingly essential to know, prevent, and treat this clinical condition. The purpose of the present review is to bring up the current evidence on the diagnosis of this pathology, in a practical way, as well as the main current treatment options.